Evaluasi Program Pembinaan Prestasi Atlet Panjat Tebing Sumatera Barat Berbasis Cippo - Sharly, Tika; Alnedral, Alnedral (Jurnal Sporta Saintika, 2022)
This research aims to evaluate the West Sumatra Rock Climbing Athlete Achievement Development Program. This evaluation was carried out to find out from the Konteks model, about the vision and mission of the West Sumatra rock climbing branch management. This research includes descriptive research. Descriptive research is research that aims to reveal or describe a problem/state/event as it is systematically. The approach used in this study is a phenomenological qualitative approach. It is said to be phenomenological, because in accordance with the purpose of research, namely dedeskrising sosial events and being able to uncover actual events in the field The purpose of this study is to evaluate the training program of west Sumatra rock climbing athletes, evaluation using the CIPPO model (Konteks, Input, Process, Product, and Outcome). The results of research in terms of Konteks Model Evaluation, the achievement coaching program of West Sumatra rock climbing athletes should unite about the vision and mission of the West Sumatra rock climbing board, because the glorious achievements start from the vision and mission of the board and work together in implementation to achieve a coaching program, design and provide solutions together without ruling out AD / ART rock climbing. Input Model Evaluation, West Sumatra rock climbing athletes' achievement coaching program in the recruitment of athletes and coaches should be open, transpransi and see from all aspects both the talents and interests of athletes and coaches, so that achievements can be carried out properly. Based on the criteria of coaching science. Evaluation of Model Process, a program to foster the achievements of West Sumatra rock climbing athletes, the need for the performance of managers with good quality control for the sake of achieving A construction program that has been designed. Evalusi Model Product, a program to foster the achievements of West Sumatra rock climbing athletes, every result obtained should be given appreciation from the management, coaches and the government so as to foster It can always be run well. Evaluation of Model Outcome, the program of coaching the achievements of Tarung Derajat athletes of Riau Province in the evaluation of athletes should be after completing coaching when not being an athlete anymore, the athlete must be able to channel the knowledge he obtained during the Become an athlete and can create a cadre of minimal quality athletes like himself, so that this coaching can run continuously. This program needs to be addressed and continued by optimizing the implementation order of the exercise program in accordance with the provisions of the latest branch administrators so that they can continue to follow the development of modern rock climbing sports. Keywords : Program Evaluation, Achievement Evaluation and Climbing Sports Coaching Cliff